Implementation of low power multi-hop wireless sensor network - Fengyong (2018)
In this paper, the multi-hop wireless sensor network is created, which is realized by Micaz and Mib520 Board using TinyOS and Cygwin. The mote transmission mode is engaged and off-the-shelf protocols and algorithm, RSSI and PDR, are applied in this wireless network and the performance is improved. Several experiments are proposed to set standard RSSI threshold value to allow the user to send packet with efficient power level.